Populisme Punitif dan Erosi Nilai-Nilai Hukum : Mengupas Kebijakan Kriminal di Tengah Polarisasi Sosial - Zul Khaidir Kadir (Pusat Riset dan Inovasi Nasional, 2025)
Punitive populism is a political-legal phenomenon that replaces legal rationality and corrective justice with a rhetoric of power that negates the protection of human rights and the rehabilitative function of the criminal justice system. In this context, criminal policy tends to be characterized by a repressive approach that prioritizes symbolic punishment for short-term political legitimacy. Social polarization further strengthens the destructive power of punitive populism by making the issue of crime a symbolic instrument in identity conflicts, thereby losing its autonomy and submitting to an emotional, majoritarian logic. This study aims to analyze how punitive populism, as a product of the interaction between populist logic and social polarization, results in the erosion of the basic values of modern law, particularly the principles of proportionality, legal certainty, and human rights protection. Furthermore, this study also identifies structural barriers that hinder efforts to curb its expansion in criminal policy. The study uses qualitative methods with a conceptual approach. Data were obtained through library research of academic literature, legal documents, and policy analysis, then processed using qualitative analysis techniques and presented descriptively. The research findings show that punitive populism has shifted the orientation of criminal policy from a paradigm of justice and rehabilitation to a logic of punishment that is reactive to public emotional distress. The mass media, particularly within a polarized information ecosystem, plays a role in shaping distorted perceptions of crime, thereby reinforcing public demands for harsh and immediate policies. This situation creates legal vulnerability to political instrumentalism, threatens the principle of the rule of law, and deepens social exclusion of vulnerable groups. To address this, strategic steps are needed, including limiting fear-based political rhetoric, strengthening independent legal institutions, and rebuilding a criminal law paradigm based on substantive justice, inclusivity, and respect for human rights.